2009
DOI: 10.1590/s0001-37652009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived antimalarial agents: new leads and efficient phythomedicines. Part I. Alkaloids

Abstract: Malaria remains one of the most serious world health problem and the major cause of mortality and morbidity in the endemic regions. Brazil is among the 30 high-burden countries and most of the cases occur in the Legal Amazonian Region. New chemotherapeutical agents are needed for the treatment of malaria. Many plant species are used in traditional medicines of malarious countries and a relatively few number of these have been investigated for evaluation of their antimalarial effect. Still lower is the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 83 publications
3
99
0
11
Order By: Relevance
“…The result of the current study revealed that the leaf extract of Albizia chevalieri prolong the survival time of an infected rat in the four day suppressive test. Plant materials that can prolong the survival time of infected experimental animals compared to the negative control are considered active agents against malaria (Oliveira et al, 2009). Which is in line with the current study.…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…The result of the current study revealed that the leaf extract of Albizia chevalieri prolong the survival time of an infected rat in the four day suppressive test. Plant materials that can prolong the survival time of infected experimental animals compared to the negative control are considered active agents against malaria (Oliveira et al, 2009). Which is in line with the current study.…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…Mean survival time is another parameter evaluates the antimalarial activity of plant extracts. Accordingly, a plant material that can prolong the survival time of infected experimental animals compared to the negative control is considered as active agent against malaria (Oliveira et al, 2009). In this study, statistically, the mice treated with 500 mg/kg of extract had significantly lived longer than negative control and this could be attributed to parasitemia suppression effect of the extract.…”
Section: Discussionmentioning
confidence: 66%
“…Among the tested extracts, the stem extracts of A. indica and J. glandulifera showed IC 50 value (43.81 毺 g/mL, 49.14 毺 g/mL respectively) at 2.3 fold and 2.6 fold concentration of positive control chloroquine respectively. This might be due to the presence of glycosides, alkaloids, flavonoids, phenol and tannins [3,[25][26][27] . According to Rasoanaivo et al 14%, 57% and 29% of extracts from medicinal plants were classified as active, weakly active and inactive respectively [22] .…”
Section: Discussionmentioning
confidence: 99%